2022
DOI: 10.3389/fimmu.2022.904481
|View full text |Cite
|
Sign up to set email alerts
|

Bat Employs a Conserved MDA5 Gene to Trigger Antiviral Innate Immune Responses

Abstract: Bats are important hosts for various zoonotic viral diseases. However, they rarely show signs of disease infection with such viruses. As the first line for virus control, the innate immune system of bats attracted our full attention. In this study, the Tadarida brasiliensis MDA5 gene (batMDA5), a major sensor for anti-RNA viral infection, was first cloned, and its biological functions in antiviral innate immunity were identified. Bioinformatics analysis shows that the amino acid sequence of batMDA5 is poorly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Avian influenza virus ( AIV ), the A/Chicken/Shanghai/010/2008 (H9N2) virus (SH010) isolated from chickens in shanghai, China, in 2008 and identified as H9N2 avian influenza A virus ( Cheng et al, 2015 ). The GFP-tagged vesicular stomatitis virus ( VSV ) VSV-GFP, was stored in our Laboratory ( Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Avian influenza virus ( AIV ), the A/Chicken/Shanghai/010/2008 (H9N2) virus (SH010) isolated from chickens in shanghai, China, in 2008 and identified as H9N2 avian influenza A virus ( Cheng et al, 2015 ). The GFP-tagged vesicular stomatitis virus ( VSV ) VSV-GFP, was stored in our Laboratory ( Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The GFP tagged vesicular stomatitis virus (VSV) VSV-GFP were stored in our Laboratory. The viruses were puri ed, propagated, and stored as described in our previous study [20].…”
Section: Cell Culture and Virusmentioning
confidence: 99%
“…However, the IKK pathway activates the P50 protein which induces NFκB activation and consequently Type I IFN production 21,42–44 . Retinoic acid inducible gene I (RIG‐I) and RIG‐I‐like proteins such as the melanoma differentiation associated protein 5 (MDA5) are important nucleic acid binding proteins that are part of the pattern recognition receptor proteins (PRRs) 45,46 . MDA5 and RIG‐I bind to viral dsRNA post infection, this binding has been shown to induce the expression of Type I IFNs 47 .…”
Section: Viral Genome‐specific Pathways In Innate Immunitymentioning
confidence: 99%
“…It was also shown that the batMDA5 genomic sequence was conserved between bats, humans, horses, and pigs (homology among mammals), however MDA5 sequences showed lower homology between bat species (inter‐species differences and evolution) 45 . Although research shows that antiviral response is highly induced in bat cell lines, 45 the ability of carrying multiple replicating viruses and being asymptomatic is still a mystery 45,48 . This lead researchers to believe that MDA5 mildly induces Type I IFN expression as a response to viral infection 45 .…”
Section: Viral Genome‐specific Pathways In Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation